1997
DOI: 10.1128/mcb.17.12.6982
|View full text |Cite
|
Sign up to set email alerts
|

Yap, a Novel Family of Eight bZIP Proteins in Saccharomyces cerevisiae with Distinct Biological Functions

Abstract: Saccharomyces cerevisiae contains eight members of a novel and fungus-specific family of bZIP proteins that is defined by four atypical residues on the DNA-binding surface. Two of these proteins, Yap1 and Yap2, are transcriptional activators involved in pleiotropic drug resistance. Although initially described as AP-1 factors, at least four Yap proteins bind most efficiently to TTACTAA, a sequence that differs at position ؎2 from the optimal AP-1 site (TGACTCA); further, a Yap-like derivative of the AP-1 facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
317
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(322 citation statements)
references
References 69 publications
3
317
0
2
Order By: Relevance
“…The three contiguous genes identified as ACR1 (YAP8), ACR2 and ACR3 encode a positive regulator, an arsenate-reductase and a plasma membrane arsenite efflux protein, respectively [2][3][4][5]. ACR1, also designated YAP8, belongs to the yeast AP-1 like factor (YAP) family of transcription factors [6]. Members of the YAP family (Yap1p to Yap8p) share a conserved bZIP DNA-binding domain, each regulating a specific set of genes involved in multi-drug resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…The three contiguous genes identified as ACR1 (YAP8), ACR2 and ACR3 encode a positive regulator, an arsenate-reductase and a plasma membrane arsenite efflux protein, respectively [2][3][4][5]. ACR1, also designated YAP8, belongs to the yeast AP-1 like factor (YAP) family of transcription factors [6]. Members of the YAP family (Yap1p to Yap8p) share a conserved bZIP DNA-binding domain, each regulating a specific set of genes involved in multi-drug resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the positive regulatory effect exerted by Yap1p and Msn2p is the Ras-cAMP-PKA pathway, which has been previously shown to negatively regulate both Yap1p (Fernandes et al, 1997) and STRE-driven induction (Gorner et al, 1998;Marchler, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous experiments with DNA microarrays demonstrated that a number of genes involved in stress response show Yap1p-dependent expression (Gasch et al, 2000), little is known about the differences between genes regulated by Yap1p versus Yap2p. Yap1p and Yap2p are 88% identical in their DNA binding regions and have both been shown to bind the same consensus site (TTAGTAA; Fernandes et al, 1997). Furthermore, overexpression of either protein induces resistance to multiple cellular stresses (Schnell et al, 1992;Bossier et al, 1993;Wu et al, 1993;Hirata et al, 1994b;Stephen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, no targets for Yap2p have yet been identified. If and how Yap1p and Yap2p show specificity toward different regulons are also unresolved questions because both proteins bind to and activate transcription from the same consensus sequence (Hirata et al, 1994b;Fernandes et al, 1997). To begin to answer these questions we used whole-genome microarrays to measure the expression of all the genes in the genome in wild-type, yap1⌬ , yap2⌬ , and yap1⌬ yap2⌬ cells grown in minimal medium.…”
Section: Introductionmentioning
confidence: 99%